Penegakan Hukum Kehutanan dalam Rangka Antisipasi Dampak Climate Change di Indonesia - I Gusti Ayu Ketut Rachmi Handayani (Fakultas Hukum Universitas Gadjah Mada, 2009)
Indonesia’s forest resources and watersheds are not contributing as they should to poverty reduction, economic and social development, and environmental sustainability. Instead, forest areas are threatened with degradation, fragmentation and destruction. A quarter of the “state forest area” lacks tree cover. In recent years, Indonesia has been losing up to 2 million hectares annually, mainly due to illegal cutting and land conversion fueled by excess processing capacity and a lack of effective management and law enforcement. Forest loss undermines rural livelihoods, ecosystem services and Indonesia’s ability to meet poverty alleviation goals. Poor forest governance damages the investment climate, rural economic potential, and Indonesia’s competitiveness and international reputation. Forest crime exacerbates problems of budget and fiscal balance, and diverts public revenues that could be better spent on poverty reduction and development goals. As Indonesia moves from transition to stabilization and growth, there is a tremendous opportunity to help the government find new ways of managing forest areas in partnership with local communities, contributing to democracy, justice, equity, rural sector investment, jobs and growth.